Konsistensi Realitas Sosial dalam Tradisi Uang Panai di Sulawesi Selatan Berdasarkan Fatwa MUI No. 02 Tahun 2022 tentang Uang Panai Terkait dengan Sila Kelima Pancasila dan Maqasid Al-Syari'ah - Muhammad; Trisnawati; Andi Muh. Taqiyuddin BN; Samsidar Jamaluddin; Ahmad Arief (STIH Zainul Hasan Kraksaan Kraksaan, 2025)
This study aims to examine the consistency of social reality in the tradition of Uang Panai’ in the South Sulawesi MUI Fatwa Number 02 of 2022 concerning Uang Panai’ with the fifth principle of Pancasila and Maqasid al-Syari’ah. This study is a qualitative research. The research design is a literature review. The results of the study indicate that; first, the concept of Uang Panai’ was originally intended to honour the bride’s family. Uang Panai’ among the Bugis people is used as wedding celebration money or commonly referred to as shopping money, with the purpose of expressing the groom’s respect for the bride. Second, based on the social reality of the Uang Panaik tradition as stated in the MUI South Sulawesi Fatwa No. 02 of 2022 on Uang Panaik, it can be concluded that this social reality is inconsistent with the fifth principle of Pancasila and the Maqasid al-Syariah. Although the initial purpose of the dowry tradition, which is to honour the bride and meet financial needs in the marriage ceremony, is considered consistent with the fifth principle of Pancasila and Maqasid al-Syari’ah.